A comparison of the suitability of cathode ray tube (CRT) and liquid crystal display (LCD) monitors as visual stimulators in mfERG diagnostics - Kaltwasser, Christoph; Horn, Folkert; Kremers, Jan; Jünemann, Anselm (Documenta Ophthalmologica, 2009)
The aim of this study was to determine up to which extent the specific characteristics of cathode ray tube (CRT) and liquid crystal display (LCD) monitors influence the retinal biosignal when used as stimulators in ocular electrophysiology. In a conventional CRT monitor, each pixel lights up only for a duration of a few milliseconds during each frame. In contrast, liquid crystal displays are quasi-static, i.e. each pixel has a constant luminance during the whole length of the frame, but lights up only with a certain delay after the trigger. These different display characteristics may affect the mfERG signal. The temporal and spatial luminance distributions of a CRT and an LCD monitor were measured in white flashes. The total amount of emitted light was calculated by integration of the intensity versus time curves. By means of an mfERG recording system (RETIsystem, Roland Consult, Brandenburg, Germany) first-order kernel (FOK) mfERG signals were computed and then analysed using customized MATLAB (TheMathWorks, Natick, MA, USA) software. With the two stimulator monitors, differences in the mfERG signal were observed. The latencies of mfERG responses recorded with the LCD monitor were significantly increased by 7.1 ms for N1 and 9.5 ms for P1 compared to the CRT. Due to a higher luminance, the N1 amplitude was significantly higher by approx. 2 dB in measurements with the LCD monitor while no significant difference could be detected with regard to the more contrast sensitive P1 amplitude. When using LCD monitors as stimulators the increase in latencies and differences in the luminance versus time profile must be taken into account. Prior to clinical application, the establishment of guidelines for the use of LCD monitors is recommended.
Keywords: CRT; LCD; Multifocal ERG; Stimulus delivery

Bias associated with the use of maximum, minimum, or range of a number of intraocular pressure measurements - Huchzermeyer, Cord; Horn, Folkert; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2011)
EVALuna2:21008

Bilateral circumscribed posterior keratoconus: visualization by ultrasound biomicroscopy and slit-scanning topography analysis - Rejdak, Robert; Nowomiejska, Katarzyna; Haszcz, Dariusz; Jünemann, Anselm (Journal of Ophthalmology, 2012)
This paper documents a rare nonprogressive developmental disorder-bilateral circumscribed posterior keratoconus-in a 60-year-old man referred for a cataract surgery. For the first time ultrasound biomicroscopy was used to visualise the local anterior bulging of the posterior corneal surface with concomitant thinning of the stroma. The amount of localized posterior depression, corneal thickness and the refractive power of both the posterior and anterior corneal curvature were measured using slit-scanning topography analysis (Orbscan).
EVALuna2:21081

Combined evaluation of frequency doubling technology perimetry and scanning laser ophthalmoscopy for glaucoma detection using automated classification - Horn, Folkert; Lämmer, Robert; Mardin, Christian; Jünemann, Anselm; Michelson, Georg; Lausen, Berthold; Adler, Werner (Journal of Glaucoma, 2012)
To develop a diagnostic setup with classification rules for combined analysis of morphology [Heidelberg Retina Tomograph (HRT)] and function [frequency doubling technology (FDT) perimetry] measurements.We used 2 independent case-control studies from the Erlangen eye department as learning and test data for automated classification using random forests. One eye of 334 open angle glaucoma patients and 254 controls entered the study. All individuals underwent HRT scanning tomography of the optic disc, FDT screening, conventional perimetry, and evaluation of fundus photographs. Random forests were learned on individuals of the Erlangen glaucoma registry (102 preperimetric patients, 130 perimetric patients, 161 controls). The classification performances of random forests and built-in classifiers were examined by receiver operator characteristic analysis on an independent second cohort of individuals (47 preperimetric patients, 55 perimetric patients, 93 controls).HRT measurements had a higher diagnostic power for early glaucomas and FDT perimetry for glaucoma patients with visual field loss. A combination of all parameters using automated classification was superior to single tests in comparison to the diagnostic instrument with the higher diagnostic power in the respective group. Highest sensitivities at a fixed specificity (95%) in the patients of the present test population were: HRT=32%, FDT=19%, combined analysis=47% in preperimetric patients and HRT=76%, FDT=89%, combined analysis=96% in perimetric patients.The feasibility of machine learning for medical diagnostic assistance could be demonstrated in patients from 2 independent study populations. A predictive model using automated classification is able to combine the advantages of morphology and function, resulting in a higher diagnostic power for glaucoma detection.
EVALuna2:5313

Confocal Laser Scanning Tomography to Predict Visual Field Conversion in Patients With Ocular Hypertension and Early Glaucoma - Schrems-Hösl, Laura-Maria; Schrems, Wolfgang; Lämmer, Robert; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Mardin, Christian (Journal of Glaucoma, 2016)
To compare Moorfields regression analysis (MRA), Glaucoma probability score (GPS), and different discriminant functions to predict future visual field conversion of patients with ocular hypertension and early glaucoma.The study included 120 eyes of patients with ocular hypertension and 110 eyes of patients with early glaucoma from the Erlangen glaucoma registry. Annually, all patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and HRT (Heidelberg Retina Tomograph I-III; Heidelberg Engineering) measurements. The cohort was divided into 2 groups based on the development of repeatable glaucomatous visual fields. Positive predictive values and negative predictive values were compared for MRA, GPS, and the classification of Bathija, Iester, Mardin, and Mikelberg at baseline. Kaplan-Meier Survival curves and Logrank tests were used to evaluate equality of survival distributions for different test results.Median follow-up was 9.04 years. 26 eyes (11.3%) demonstrated glaucomatous visual field loss in the follow-up. MRA temporal-superior and temporal-inferior outside normal limits were predictive of future visual field loss with positive predictive values of 33.3% and 28.6%. Normal GPS Temporal Sector demonstrated a negative predictive value of 96.4% and normal results in discriminant functions between 94.7% and 95.5%.Confocal scanning laser tomography is a useful imaging modality to predict future visual field conversion. Development of visual field defects in 10 years is highly unlikely, if GPS classification and/or classification of discriminant analysis at baseline are normal. MRA temporal-superior and temporal-inferior outside normal limits are associated with future VF conversion (ClinicalTrials.gov number, NTC00494923).
EVALuna2:21172

Correlation between Loss of the Retinal Nerve Fiber Layer Thickness and Local Visual Field Defects measured with FDF-Perimetry - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 642 perimetry; 610 nerve fiber layer; 758 visual fields

Diagnosis and therapy of pseudoexfoliation glaucoma - Jünemann, Anselm (Ophthalmologe, 2012)
Pseudoexfoliation (PEX) glaucoma is the most frequent and most important type of secondary glaucoma, accounting for approximately 25% of open angle glaucoma worldwide and currently representing the most common identifiable cause of glaucoma overall. Due to high intraocular pressure levels, marked diurnal pressure fluctuations and spikes, and rapid optic nerve damage and visual field loss, PEX glaucoma represents a relatively severe and progressive type of glaucoma. Therefore, hard and fast lowering of intraocular pressure is necessary. Fixed combinations in medical therapy and early glaucoma surgery are recommended. When considering a surgical procedure (e.g. selective laser trabeculoplasty, bleb-dependent or bleb-independent surgery) the timing of cataract surgery plays a major role. Pathogenesis, clinical characteristics and therapeutic aspects of PEX glaucoma are described in the following article.
EVALuna2:21092

Dyslipidaemia and glaucoma - Jünemann, Anselm; Huchzermeyer, Cord; Rejdak, R.; Hohberger, B. (Klinische Monatsblätter für Augenheilkunde, 2014)
Endothelial dysfunction and vascular dysregulation play a role in the multifactorial pathogenesis of glaucomatous optic nerve atrophy. Dyslipidaemia as a risk factor for endothelial dysfunction is associated with glaucoma and cardiovascular morbidity and mortality. In additional to a genetic disposition, a potential mechanism for the pathogenesis of endothelial dysfunction could be an additive effect of several risk factors, like dyslipidaemia, smoking, arterial hypertension, diabetes and hyperhomocysteinaemia. This paper reviews the literature concerning the association between dyslipidaemia and glaucomatous disease and explains the possible role of dyslipidaemia for the pathogenesis and progression of glaucoma. The role of exogeneous modifiable risk factors for prevention and therapy of glaucoma and their neutralisation by changing life style like weight reduction, modifications of nutrition and physical activity, are discussed.
EVALuna2:21178

Elevated vitreous body glial fibrillary acidic protein in retinal diseases - Jünemann, Anselm; Rejdak, Robert; Huchzermeyer, Cord; Maciejewski, Ryszard; Grieb, Pawel; Kruse, Friedrich; Zrenner, Eberhart; Rejdak, Konrad; Petzold, Axel (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
Increased expression of glial fibrillary acidic protein (GFAP) is a characteristic of gliotic activation (Müller cells and astrocytes) in the retina. This study assessed vitreous body GFAP levels in various forms of retinal pathology.This prospective study included 82 patients who underwent vitrectomy (46 retinal detachments (RDs), 13 macular hole (MHs), 15 epiretinal glioses (EGs), 8 organ donors). An established enzyme-linked immunosorbent assay (ELISA, SMI26) was used for quantification of GFAP.The highest concentration of vitreous body GFAP in organ donors was 20 pg/mL and it was used as the cutoff. A significant proportion of patients suffering from RD (65 %) to EG (53 %) had vitreous body GFAP levels above this cutoff when compared to organ donors (0 %, p < 0.0001, p = 0.0194, respectively, Fisher's exact test) and MH (8 %, p < 0.0001, p = 0.0157, respectively). In RD and EG, vitreous body GFAP levels were correlated with axial length (R = 0.69, R = 0.52, p < 0.05 for both).The data suggest that human vitreous body GFAP is a protein biomarker for glial activation in response to retinal pathologies. Vitreous body GFAP levels may be of interest as a surrogate outcome for experimental treatment strategies in translational studies.
EVALuna2:21235

Evacuating a pre-Descemet hematoma through a clear corneal incision during a canaloplasty procedure - Rekas, Marek; Petz, Katarzyna; Wierzbowska, Joanna; Byszewska, Anna; Jünemann, Anselm (Journal of Cataract and Refractive Surgery, 2014)
We present a surgical technique for evacuating an intracorneal pre-Descemet hematoma that occurred during a canaloplasty procedure. The technique allows both evacuation of the hematoma outside the anterior chamber and preservation of the intact Descemet membrane, and it can be performed within the primary procedure. Intraoperative pre-Descemet hematoma is reported to be a relatively rare complication of canaloplasty; however, to hasten visual recovery and to avoid potentially sight-threatening complications, surgeons should be aware of this possible complication and be prepared to resolve it as early as possible, even within the canaloplasty procedure.No author has a financial or proprietary interest in any material or method mentioned.
EVALuna2:21210

Flicker-defined form perimetry in glaucoma patients - Horn, Folkert; Kremers, Jan; Mardin, Christian; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
To assess the potential of flicker-defined form (FDF) perimetry to detect functional loss in patient groups with beginning glaucoma, and to evaluate the dynamic range of the FDF stimulus in individual patients and at individual test positions.FDF perimetry and standard automated perimetry (SAP) were performed at identical test locations (adapted G1 protocol) in 60 healthy subjects and 111 glaucoma patients. All patients showed glaucomatous optic disc appearance. Grouping within the glaucoma cohort was based on SAP-performance: 33 "preperimetric" open-angle glaucoma (OAG) patients, 28 "borderline" OAG (focal defects and SAP-mean defect (MD) <2 dB), 33 "early" OAG (SAP-MD < 5 dB), 17 "advanced" OAG. All participants were experienced in psychophysical and perimetric tests. Defect values and the areas under receiver operating characteristic curves (ROC) in patient groups were statistically compared.The values of FDF-MD in the preperimetric, borderline, and early OAG group were 2.7 ± 3.4 dB, 5.5 ± 2.6 dB, and 8.5 ± 3.4 dB respectively (all significantly above normal). The percentage of patients exceeding normal FDF-MD was 27.3 %, 60.7 %, and 87.9 % respectively. The age-adjusted FDF-mean defect (MD) of the G1X-protocol was not significantly correlated with refractive error, lens opacity, pupil size, or gender. Occurrence of ceiling effects (inability to detect targets at highest contrast) showed a high correlation with visual field losses (R = 0.72, p < 0.001). Local analysis indicates that SAP losses exceeding 5 dB could not be distinguished with the FDF technique.The FDF stimulus was able to detect beginning glaucoma damage. Patients with SAP-MD values exceeding 5 dB should be monitored with conventional perimetry because of its larger dynamic range.
EVALuna2:5485

Frequency dependency of temporal contrast adaptation in normal subjects - Hohberger, Bettina; Roessler, Christopher W.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Vision research, 2011)
The aim of this study was to determine the influence of temporal frequency of temporal contrast adaptation on contrast sensitivity in healthy subjects. Temporal contrast sensitivities (TCS) were measured monocularly in seven healthy subjects with a modified ERG full-field bowl stimulator at eight different test temporal frequencies (9, 15, 20, 25, 31, 37, 44, 51 Hz) using a two-alternative-forced-choice strategy. Before each presentation of the test stimulus, a 100% contrast adapting flicker stimulus was presented (frequencies: 9, 15, 20, 25, 31, 37, 44, 51, 100 Hz). At each adapting frequency, a complete set of TCSs was measured. All temporal contrast sensitivities decreased with increasing temporal frequencies. Adaptation led to a general temporal contrast sensitivity decrease. Largest adaptation effects were seen at an adaptation frequency of 25 Hz. Reduction of contrast sensitivity was significantly larger at 25 Hz adaptation than at 9 Hz adaptation (t-test of paired samples, Bonferroni corrected). The results of this study showed a general TCS decrease with the largest effect at an adaptation frequency of 25 Hz. This finding indicates that the contrast adaptation probably occurred in the magnocellular-pathway. In future clinical studies adaptation effects could be investigated in patients with reduced temporal contrast sensitivity.
EVALuna2:21010

Frequency doubling technique perimetry and spectral domain optical coherence tomography in patients with early glaucoma - Horn, Folkert; Mardin, C. Y.; Bendschneider, D.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Eye, 2011)
PurposeTo assess the combined diagnostic power of frequency-doubling technique (FDT)-perimetry and retinal nerve fibre layer (RNFL) thickness measurements with spectral domain optical coherence tomography (SDOCT).MethodsThe study included 330 experienced participants in five age-related groups: 77 'preperimetric' open-angle glaucoma (OAG) patients, 52 'early' OAG, 50 'moderate' OAG, 54 ocular hypertensivepatients, and 97 healthy subjects. For glaucoma assessment in all subjects conventional perimetry, evaluation of fundus photographs, FDT-perimetry and RNFL thickness measurement with SDOCT was done. Glaucomatous visual field defects were classified using the Glaucoma Staging System. FDT evaluation used a published method with casewise calculation of an 'FDT-score', including all missed localized probability levels. SDOCT evaluation used mean RNFL thickness and a new individual SDOCT-score considering normal confidence limits in 32 sectors of a peripapillary circular scan. To examine the joined value of both methods a combined score was introduced. Significance of the difference between Receiver-operating-characteristic (ROC) curves was calculated for a specificity of 96%.ResultsSensitivity in the preperimetric glaucoma group was 44% for SDOCT-score, 25% for FDT-score, and 44% for combined score, in the early glaucoma group 83, 81, and 89%, respectively, and in the moderate glaucoma group 94, 94, and 98%, respectively, all at a specificity of 96%. ROC performance of the newly developed combined score is significantly above single ROC curves of FDT-score in preperimetric and early OAG and above RNFL thickness in moderate OAG.ConclusionCombination of function and morphology by using the FDT-score and the SDOCT-score performs equal or even better than each single method alone.
EVALuna2:5300

Glaucoma Diagnostic Performance of GDxVCC and Spectralis OCT on Eyes With Atypical Retardation Pattern - Hoesl, Laura Maria; Tornow, Ralf-Peter; Schrems, Wolfgang; Horn, Folkert; Mardin, Christian; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Journal of Glaucoma, 2013)
: To investigate the impact of typical scan score (TSS) on discriminating glaucomatous and healthy eyes by scanning laser polarimetry and spectral domain optical coherence tomography (SD-OCT) in 32 peripapillary sectors.: One hundred two glaucoma patients and 32 healthy controls underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, GDxVCC, and SD-OCT measurements. For controls, only very typical scans (TSS=100) were accepted. Glaucoma patients were divided into 3 subgroups (very typical: TSS=100; typical: 99>=TSS>=80, atypical: TSS<80). Receiver operating characteristic curves were constructed for mean retinal nerve fiber layer values, sector data, and nerve fiber indicator (NFI). Sensitivity was estimated at >=90% specificity to compare the discriminating ability of each imaging modality.: For discrimination between healthy and glaucomatous eyes with very typical scans, the NFI and inferior sector analyses 26 to 27 demonstrated the highest sensitivity at >=90% specificity in GDxVCC and SD-OCT, respectively. For the typical and atypical groups, sensitivity at >>=90% specificity decreased for all 32 peripapillary sectors on an average by 10.9% and 17.9% for GDxVCC and by 4.9% and 0.8% for SD-OCT. For GDxVCC, diagnostic performance of peripapillary sectors decreased with lower TSS, especially in temporosuperior and inferotemporal sectors (sensitivity at >=90% specificity decreased by 55.3% and by 37.8% in the atypical group).: Diagnostic accuracy is comparable for SD-OCT and GDxVCC if typical scans (TSS=100) are investigated. Decreasing TSS is associated with a decrease in diagnostic accuracy for discriminating healthy and glaucomatous eyes by scanning laser polarimetry. NFI is less influenced than the global or sector retinal nerve fiber layer thickness. The TSS score should be included in the standard printout. Diagnostic accuracy of SD-OCT is barely influenced by low TSS.
EVALuna2:21037

Influence of mode of delivery on pre-existing eye diseases - Jünemann, Anselm; Sterk, N.; Rejdak, R. (Ophthalmologe, 2012)
Many ophthalmologists and obstetricians recommend either an assisted vaginal delivery with forceps or vacuum extraction, or a Caesarean section in cases of pre-existing eye diseases, such as myopia, retinal detachment, glaucoma or diabetic retinopathy. This is mainly based on the increase of intraocular pressure during the final stage of labor. These recommendations, however, are not evidence-based. None of the published trials have reported any retinal changes after vaginal delivery. This report provides information on the influence of physiological changes on eye diseases during the final stage of delivery. In general eye disease is not an indication for an instrumental or operative delivery provided regular eye examinations (once each trimester) have been performed.
EVALuna2:21064

Levels of Aqueous Humor Trace Elements in Patients with Non-Exsudative Age-related Macular Degeneration: A Case-control Study - Jünemann, Anselm; Stopa, Piotr; Michalke, Bernhard; Chaudhri, Anwar; Reulbach, Udo; Huchzermeyer, Cord; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Zrenner, Eberhart; Rejdak, Robert (PLoS ONE, 2013)
Trace elements might play a role in the complex multifactorial pathogenesis of age-related macular degeneration (AMD). The aim of this study was to measure alterations of trace elements levels in aqueous humor of patients with non-exsudative (dry) AMD.For this pilot study, aqueous humor samples were collected from patients undergoing cataract surgery. 12 patients with dry AMD (age 77.9±6.62, female 8, male 4) and 11 patients without AMD (age 66.6±16.7, female 7, male 4) were included. Aqueous levels of cadmium, cobalt, copper, iron, manganese, selenium, and zinc were measured by use of Flow-Injection-Inductively-Coupled-Plasma-Mass-Spectrometry (FI-ICP-MS), quality controlled with certified standards.PATIENTS WITH AMD HAD SIGNIFICANTLY HIGHER AQUEOUS HUMOR LEVELS OF CADMIUM (MEDIAN: 0.70 µmol/L, IQR: 0.40-0.84 vs. 0.06 µmol/L; IQR: 0.01-.018; p = 0.002), cobalt (median: 3.1 µmol/L, IQR: 2.62-3.15 vs. 1.17 µmol/L; IQR: 0.95-1.27; p<0.001), iron (median: 311 µmol/L, IQR: 289-329 vs. 129 µmol/L; IQR: 111-145; p<0.001) and zinc (median: 23.1 µmol/L, IQR: 12.9-32.6 vs. 5.1 µmol/L; IQR: 4.4-9.4; p = 0.020) when compared with patients without AMD. Copper levels were significantly reduced in patients with AMD (median: 16.2 µmol/L, IQR: 11.4-31.3 vs. 49.9 µmol/L; IQR: 32.0-.142.0; p = 0.022) when compared to those without. No significant differences were observed in aqueous humor levels of manganese and selenium between patients with and without AMD. After an adjustment for multiple testing, cadmium, cobalt, copper and iron remained a significant factor in GLM models (adjusted for age and gender of the patients) for AMD.Alterations of trace element levels support the hypothesis that cadmium, cobalt, iron, and copper are involved in the pathogenesis of AMD.
EVALuna2:21116

Longitudinal analysis of progression in glaucoma using spectral-domain optical coherence tomography - Wessel, Julia M.; Horn, Folkert; Tornow, Ralf-Peter; Schmid, Matthias; Mardin, Christian; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Investigative Ophthalmology & Visual Science, 2013)
To compare the longitudinal loss of RNFL thickness measurements by SD-OCT in healthy individuals and glaucoma patients with or without progression concerning optic disc morphology.A total of 62 eyes, comprising 38 glaucomatous eyes with open angle glaucoma and 24 healthy controls, were included in the study (Erlangen Glaucoma Registry, NTC00494923). All patients were investigated annually over a period of 3 years by Spectralis SD-OCT measuring peripapillary RNFL thickness. By masked comparative analysis of photographs, the eyes were classified into nonprogressive and progressive glaucoma cases. Longitudinal loss of RNFL thickness was compared with morphological changes of optic disc morphology.Mixed model analysis of annual OCT scans revealed an estimated annual decrease of the RNFL thickness by 2.12 ?m in glaucoma eyes with progression, whereas glaucoma eyes without progression in optic disc morphology lost 1.18 ?m per year in RNFL thickness (P = 0.002). The rate of change in healthy eyes was 0.60 ?m and thereby also significantly lower than in glaucoma eyes with progression (P < 0.001). The intrasession variability of three successive measurements without head repositioning was 1.5 ± 0.7 ?m. The loss of mean RNFL thickness exceeded the intrasession variability in 60% of nonprogressive eyes, and in 85% of progressive eyes after 3 years.LONGITUDINAL MEASUREMENTS OF RNFL THICKNESS USING SD-OCT SHOW A MORE PRONOUNCED REDUCTION OF RNFL THICKNESS IN PATIENTS WITH PROGRESSION COMPARED WITH PATIENTS WITHOUT PROGRESSION IN GLAUCOMATOUS OPTIC DISC CHANGES. (www.clinicaltrials.gov number, NTC00494923.).
EVALuna2:5384

Longitudinal stability of the diurnal rhythm of intraocular pressure in subjects with healthy eyes, ocular hypertension and pigment dispersion syndrome - Huchzermeyer, Cord; Reulbach, Udo; Horn, Folkert; Lämmer, Robert; Mardin, Christian; Jünemann, Anselm (Bmc Ophthalmology, 2014)
The diurnal fluctuation of intraocular pressure may be relevant in glaucoma. The aim of this study was to find out whether the timing of diurnal fluctuation is stable over the years.Long-term IOP data from the Erlangen Glaucoma Registry, consisting of several annual extended diurnal IOP profiles for each patient, was retrospectively analyzed. Normal subjects, patients with ocular hypertension and with pigment dispersion syndrome were included because these subjects had not been treated with antiglaucomatous medications at the time of data acquisition. A cosine curve was fitted to the IOP data and the stability of individual rhythms over the years was tested using the Rayleigh test. To compare the peak times among groups, means were calculated only from subjects with a significant Rayleigh test.Of the fifty-two eligible subjects, a total of 364 extended diurnal IOP profiles measured in a sitting position had been collected over a period of 114 ± 39 months. The Rayleigh test indicated intraindividual stability of phase timing only in 19 subjects (36%). In subjects with pigment dispersions syndrome, peak IOP occurred on average two hours and seven minutes later during the day compared with subjects without this condition (p = 0.05).Fitting of cosine curves to the clinical IOP profiles was generally feasible, although careful interpretation is warranted due to lack of measurements in supine position and between midnight and 7 am. The interesting observation of a phase lag in eyes with pigment dispersion syndrome warrants confirmation and exploration in future prospective studies. The analysis of the IOP data showed no stable individual rhythm in the long term in a majority of patients.
EVALuna2:21175

Long Term Follow-Up of Preperimetric Open-Angle Glaucoma: Improvement of the Visual Field in Morphological Stable Patients Only - Jünemann, Anselm; Bellios, N.; Lämmer, Robert; Link, B.; Mardin, C. Y.; Kremers, Jan; Kruse, Friedrich; Horn, Folkert (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields

Medicinal glaucoma therapy. What can we learn from large randomized clinical trials? - Jünemann, Anselm; Huchzermeyer, Cord; Rejdak, R. (Ophthalmologe, 2013)
The prospective multicenter randomized controlled clinical trials (RCTs) Ocular Hypertension Glaucoma Treatment Study (OHTS), Early Manifest Glaucoma Trial (EMGT), Advanced Glaucoma Intervention Study (AGIS), Collaborative Initial Glaucoma Treatment Study (CITGS) and Collaborative Normal Tension Glaucoma Study (CNGTS) are often named as landmarks for glaucoma management as the results of these studies provided the evidence for numerous therapeutic decisions in clinical practice. The studies confirmed the consensus that reduction of intraocular pressure reduces the risk of glaucoma progression covering the whole spectrum of glaucoma from ocular hypertension to advanced glaucoma. Furthermore, the identification of new risk factors allows a higher precision of assessment of the risk of progression. The RCTs achieved the main goal of high level of evidence, thus making progress in the understanding of glaucoma and its treatment and bridging consensus-based and evidence-based decisions. However, the implementation of the results into clinical practice needs adequate and accurate interpretation of the results.
EVALuna2:21167

Objective perimetry using a four-channel multifocal VEP system: correlation with conventional perimetry and thickness of the retinal nerve fibre layer - Horn, Folkert; Kaltwasser, Christoph; Jünemann, Anselm; Kremers, Jan; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2012)
There is evidence that multifocal visual evoked potentials (VEPs) can be used as an objective tool to detect visual field loss. The aim of this study was to correlate multifocal VEP amplitudes with standard perimetry data and retinal nerve fibre layer (RNFL) thickness.Multifocal VEP recordings were performed with a four-channel electrode array using 58 stimulus fields (pattern reversal dartboard). For each field, the recording from the channel with maximal signal-to-noise ratio (SNR) was retained, resulting in an SNR optimised virtual recording. Correlation with RNFL thickness, measured with spectral domain optical coherence tomography and with standard perimetry, was performed for nerve fibre bundle related areas.The mean amplitudes in nerve fibre related areas were smaller in glaucoma patients than in normal subjects. The differences between both groups were most significant in mid-peripheral areas. Amplitudes in these areas were significantly correlated with corresponding RNFL thickness (Spearman R=0.76) and with standard perimetry (R=0.71).The multifocal VEP amplitude was correlated with perimetric visual field data and the RNFL thickness of the corresponding regions. This method of SNR optimisation is useful for extracting data from recordings and may be appropriate for objective assessment of visual function at different locations.This study has been registered at http://www.clinicaltrials.gov (NCT00494923).
EVALuna2:21033

Objective visual field determination in forensic ophthalmology with an optimized 4-channel multifocal VEP perimetry system: a case report of a patient with retinitis pigmentosa - Kaltwasser, C.; Horn, Folkert; Kremers, Jan; Jünemann, Anselm; Bergua, A. (Documenta Ophthalmologica, 2011)
We present the case of a 59-year-old male patient with progressive vision impairment and consecutive visual field narrowing ("tunnel view") for 7 years and a known retinitis pigmentosa for 5 years. The remaining Goldmann perimetric visual field at time reported was less than 5°. A request for blindness-related social benefits was rejected because an ophthalmologic expert assessment suggested malingering. This prompted us to assess an objective determination of the visual field using multifocal VEPs. Objective visual field recordings were performed with a four-channel multifocal VEP-perimeter using 58 stimulus fields (pattern reversal dartboard stimulus configuration). The correlated signal data were processed using an off-line method. At each field, the recording from the channel with the maximal signal-to-noise ratio (SNR) was retained, thus resulting in an SNR optimized virtual recording. Analysis of VEP signals was performed for each single field and concentric rings and compared to an average response measured in five healthy subjects. Substantial VEP responses could be identified in three fields within the innermost ring (eccentricity, 1.7°) for both eyes, although SNR was generally low. More eccentric stimuli did not elicit reliable VEP responses. The mfVEP recording was correlated with perimetric visual field data. The current SNR optimization by using the channel with the largest SNR provides a good method to extract useful data from recordings and may be appropriate for the use in forensic ophthalmology.
EVALuna2:21039

On and off responses of the photopic fullfield ERG in normal subjects and glaucoma patients - Horn, Folkert; Gottschalk, Kristina; Mardin, Christian; Pangeni, Gobinda; Jünemann, Anselm; Kremers, Jan (Documenta Ophthalmologica, 2011)
Recent studies suggest a diagnostic value of the photopic negative response (PhNR) with a long-duration stimulus. The aim of this study was to record the on and off responses of the photopic fullfield electroretinogram (ERG) in normal subjects and glaucoma patients. We focused on different waves of the responses after onset and offset of the long-duration stimulus ERG. Photopic fullfield ERGs were recorded in response to a white bright LED flash on a white 20 cd/m(2) background. Stimulus luminances were 40, 60 and 80 cd/m(2). Responses were averaged using a flash duration of 240 ms and an offset period of 500 ms. We examined 19 healthy subjects, 27 patients with glaucomatous optic disc atrophy and 7 ocular hypertensive patients. The amplitudes and implicit times of the on and off responses of the human ERG depended on flash luminance. Comparing patients with glaucoma and healthy subjects for the 60 cd/m² flash, there was a significant change in the PhNRs (at onset: P < 0.01, at offset: P < 0.001) of the d-wave and of the i-wave at offset (P < 0.01). No significant difference was found for peak times of the fullfield ERG and for a- and b-wave amplitudes. PhNR amplitudes were significantly correlated with mean thickness of retinal nerve fibre layer as measured with OCT. In comparison with the normal photopic long-flash ERG, glaucoma patients showed changes in the PhNR amplitude following stimulus onset and in waves following stimulus offset.
EVALuna2:20998
Keywords: Electroretinogram; Glaucoma; Onset/offset fullfield ERG; Photopic negative response

Pattern electroretinograms during the cold pressor test in normals and glaucoma patients - La Mancusa, Antonia; Horn, Folkert; Kremers, Jan; Huchzermeyer, Cord; Rudolph, Michael; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2014)
To examine the influence of the cold pressor test (CPT) on steady-state pattern electroretinograms (PERG) in healthy subjects and glaucoma patients.Steady-state PERGs to 7.8 Hz pattern reversal stimuli were recorded in 63 subjects. Fifteen healthy control subjects, 14 patients with ocular hypertension (OHT), and 34 patients with open-angle glaucoma (20 normotensive [NTG] and 14 high tension glaucoma [HTG]) were examined. Steady-state PERG amplitudes and latencies were analyzed at baseline, during cold stimulus using a modified CPT, and during the subsequent recovery phase. Blood pressure and heart rate were simultaneously recorded in 10 normals and 11 glaucoma patients.During the three test conditions (baseline, ice water, and warm water) glaucoma patients (NTG and HTG) showed significantly reduced PERG amplitudes in comparison with control subjects (P < 0.001) and with OHT patients (P < 0.004). Patients with OHT displayed lower PERG amplitudes than control subjects (nonsignificant, with consideration of Bonferroni). Only NTG patients showed a significant effect of the CPT on PERG amplitude (significant decrease during warm water P = 0.02). Latencies shortened significantly during warm-water period after cold stimulus in control subjects (P = 0.05) and in NTG patients (P = 0.02) with a nonsignificant trend of shortened latencies in the OHT (P = 0.06) and HTG groups (P = 0.3). Systolic and diastolic blood pressure increased during cold water (P < 0.001) and decreased during warming-up conditions (P < 0.001).This study shows that a CPT influences the PERG responses particularly in NTG. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21162

Perimetric measurements with flicker-defined form stimulation in comparison with conventional perimetry and retinal nerve fiber measurements - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
We compared the results of flicker-defined form (FDF) perimetry with standard automated perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness measurements using spectral domain optical coherence tomography (OCT).A total of 64 healthy subjects, 45 ocular hypertensive patients, and 97 "early" open-angle glaucoma (OAG) patients participated in this study. Definition of glaucoma was based exclusively on glaucomatous optic disc appearance. All subjects underwent FDF perimetry, SAP, and peripapillary measurements of the RNFL thickness. The FDF perimetry and SAP were performed at identical test locations (G1 protocol). Exclusion criteria were subjects younger than 34 years, SAP mean defect (SAP MD) > 5 dB, eye diseases other than glaucoma, or nonreliable FDF measurements. The correlations between the perimetric data on one hand and RNFL thicknesses on the other hand were analyzed statistically.The age-corrected sensitivity values and the local results from the controls were used to determine FDF mean defect (FDF MD). The FDF perimetry and SAP showed high concordance in this cohort of experienced patients (MD values, R = -0.69, P < 0.001). Of a total of 42 OAG patients with abnormal SAP MD, 38 also displayed abnormal FDF MD. However, FDF MD was abnormal in 28 of 55 OAG patients with normal SAP MD. The FDF MD was significantly (R = -0.61, P < 0.001) correlated with RNFL thickness with a (nonsignificantly) larger correlation coefficient than conventional SAP MD (R = -0.48, P < 0.001).The FDF perimetry is able to uncover functional changes concurrent with the changes in RNFL thickness. The FDF perimetry may be an efficient functional test to detect early glaucomatous nerve atrophy. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21150

Pigment dispersion syndrome and pigmentary glaucoma. Morphometric analysis of the anterior chamber segment with SL-OCT - Birner, Barbara; Tourtas, T.; Wessel, J. M.; Jünemann, Anselm; Mardin, Christian; Kruse, Friedrich; Lämmer, Robert (Ophthalmologe, 2014)
The purpose of this study was to analyze if anterior chamber parameters are risk factors for the development of pigment dispersion syndrome (PDS) and/or for the conversion to pigmentary glaucoma (PG).This study included a total of 63 eyes from 35 patients with PDS and PG and 65 eyes from 49 unaffected volunteers as the control group. The following parameters were measured by slit lamp optical coherence tomography (SL-OCT): anterior chamber volume (ACV) and depth (ACD), angle opening distance (AOD) and the trabecular iris space area (TISA) at 500 µm and 750 ?m from the scleral spur. Comparisons between the following groups were performed: between the PDS/PG and the control group, between PDS and PG and between male and female patients.The results of ACV, ACD, AOD and TISA were significantly higher in PDS/PG patients when compared to the control group. There were no significant differences between PDS and PG. The gender-specific comparison also showed no significant differences.Significantly higher anterior chamber parameters are a possible risk factor for development of PDS; however, a higher risk of conversion to PG does not seem to correlate with increased anterior chamber parameters. The parameters of the anterior chamber are apparently not associated with the male predominance of PDS and PG.
EVALuna2:21131

PKCζ-interacting protein ZIP3 is generated by intronic polyadenylation, and is expressed in the brain and retina of the rat. - Urbanczyk, Andreas; Jünemann, Anselm; Enz, Ralf (Biochemical Journal, 2011)
Scaffold proteins contain multiple protein - protein interaction modules that physically assemble functionally related proteins into larger complexes. ZIPs [PKC (protein kinase C) ζ-interacting proteins] link the enzymatic activity of the atypical PKC isoforms PKCλ/ι or PKCζ to target proteins and are associated with neurodegenerative disorders. In the rat, alternative splicing generates three ZIP variants. Previously, we identified the ZIP3 transcript, containing 13 C-terminal amino acids encoded by intron 4, in the rat CNS (central nervous system). In the present study, we identified intronic polyadenylation signals in rat and hu man ZIP genes [known as SQSTM1 (sequestosome-1) in humans] and detected the corresponding ZIP3-like transcripts. In addition, we generated ZIP3-specific immune sera and observed expression of the protein in the brain and retina of the adult rat. In the retina, ZIP3 is present in nuclear layers where it co-localizes with PKCζ. An immune serum recognizing all three ZIP isoforms labelled the same cells as the newly generated ZIP3-specific antibodies and, in addition, stained both synaptic layers of the retina. There, ZIPs are localized in axon terminals of rod bipolar cells that also contain ZIP-interacting PKCζ and GABA C (γ-aminobutyric acid type C) receptors. In summary, we detected ZIP3-like transcripts in ratand human-derived samples and describe the expression of ZIP3 in the rat CNS. © The Authors Journal compilation © 2011 Biochemical Society.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.pkc950
Keywords: γ-aminobutyric acid type C (GABA; p62; Protein kinase Cζ-interacting protein 3 (ZIP3); Retina; Sequestosome-1 (SQSTM1)

Presence of L-kynurenine aminotransferase III in retinal ganglion cells and corpora amylacea in the human retina and optic nerve - Rejdak, Robert; Rummelt, Carmen; Zrenner, Eberhart; Grieb, Pawel; Rejdak, Konrad; Okuno, Etsuo; Thaler, Sebastian; Nowomiejska, Katarzyna; Kruse, Friedrich; Turski, Waldemar; Jünemann, Anselm (Folia Neuropathologica, 2011)
Corpora amylacea (CAm) are a hallmark of aging and neurodegeneration. The presence of kynurenine aminotransferases I and II (KAT I and II) in CAm in the human retina and optic nerve has been already shown. The present study aimed to examine kynurenine aminotransferase III (KAT III) immunoreactivity in CAm in the human retina and optic nerve.Polyclonal antibody against KAT III was used on sections of human eyes enucleated due to malignant uveal melanoma. PAS-stained sections of CAm were compared with KAT III stained ones.KAT III immunoreactivity was observed in CAm in the retina, prelaminar, laminar and retrolaminar region of the optic nerve with similar location to PAS-stained sections. The most intense staining was observed in the retrolaminar part of the optic nerve. KAT III immunoreactivity was also present in the cytoplasm of retinal ganglion cells.Expression of KAT III in CAm in the human retina and optic nerve indicates that this enzyme may be relevant in mechanisms of neurodegeneration leading to CAm formatio
EVALuna2:21028

Prospective, unmasked evaluation of the iStent® inject system for open-angle glaucoma: synergy trial - Voskanyan, Lilit; Garcia-Feijoo, Julian; Belda, Jose I.; Fea, Antonio; Jünemann, Anselm; Baudouin, Christophe (Advances in Therapy, 2014)
Micro-invasive glaucoma surgical implantation of trabecular micro-bypass stents, previously shown to be safe and effective for open-angle glaucoma (OAG) subjects during cataract surgery, was considered for evaluation as a sole procedure. The aim of this study was to evaluate the safety and intraocular pressure (IOP)-lowering efficacy after ab interno implantation of two Glaukos Trabecular Micro-Bypass iStent inject second generation devices in subjects with OAG. This study was performed at sites in France, Germany, Italy, Republic of Armenia, and Spain.In this pan-European, multi-center prospective, post-market, unmasked study, 99 patients with OAG on at least two topical ocular hypotensive medications who required additional IOP lowering to control glaucoma disease underwent implantation of two GTS400 stents in a stand-alone procedure. Patients were qualified if they presented with preoperative mean IOP between 22 and 38 mmHg after medication washout. Postoperatively, subjects were assessed at Day 1, Months 1, 3, 6, 7, 9, and 12. IOP, medication use and safety were assessed at each visit.Sixty-six percent of subjects achieved IOP <=18 mmHg at 12 months without medication, and 81% of subjects achieved Month 12 IOP <= 18 mmHg with either a single medication or no medication. Mean baseline washout IOP values decreased by 10.2 mmHg or 39.7% from 26.3 (SD 3.5) mmHg to 15.7 (SD 3.7) mmHg at Month 12. Mean IOP at 12 months was 14.7 (SD 3.1) mmHg in subjects not using ocular hypotensive medications. Reduction from preoperative medication burden was achieved in 86.9% of patients, including 15.2% with reduction of one medication and 71.7% with reduction of two or more medications. Postoperative complications occurred at a low rate and resolved without persistent effects.In this series, implantation of two trabecular micro-bypass second generation stents in subjects with OAG resulted in IOP and medication reduction and favorable safety outcomes.
EVALuna2:21163

Prospective unmasked randomized evaluation of the iStent inject (®) versus two ocular hypotensive agents in patients with primary open-angle glaucoma - Fea, Antonio M.; Belda, Jose I.; Rekas, Marek; Jünemann, Anselm; Chang, Lydia; Pablo, Luis; Voskanyan, Lilit; Katz, L. Jay (Clinical Ophthalmology, 2014)
The purpose of this study was to compare outcomes of subjects with open-angle glaucoma (OAG) not controlled on one medication who underwent either implantation of two iStent inject (®) trabecular micro-bypass devices or received medical therapy consisting of a fixed combination of latanoprost/timolol.Of 192 subjects who qualified for the study and were enrolled, 94 were randomized to surgery with implantation of two iStent inject(®) devices in the treated eye and 98 to receive medical therapy.At the month 12 visit, 94.7% of eyes (89/94) in the stent group reported an unmedicated intraocular pressure (IOP) reduction of >=20% versus baseline unmedicated IOP, and 91.8% of eyes (88/98) in the medical therapy group reported an IOP reduction >=20% versus baseline unmedicated IOP. A 17.5% between-group treatment difference in favor of the iStent inject group was statistically significant (P=0.02) at the >=50% level of IOP reduction. An IOP <=18 mmHg was reported in 92.6% of eyes (87/94) in the iStent inject group and 89.8% of eyes (88/98) in the medical therapy group. Mean (standard deviation) IOP decreases from screening of 8.1 (2.6) mmHg and 7.3 (2.2) mmHg were reported in the iStent inject and medical therapy groups, respectively. A high safety profile was also noted in this study in both the iStent inject and medical therapy groups, as measured by stable best corrected visual acuity, cup-to-disc ratio, and adverse events.These data show that the use of iStent inject is at least as effective as two medications, with the clinical benefit of reducing medication burden and assuring continuous treatment with full compliance to implant therapy as well as having a highly favorable safety profile.
EVALuna2:21209

Regulation of Lysyl Oxidase-like 1 (LOXL1) and Elastin-Related Genes by Pathogenic Factors Associated with Pseudoexfoliation Syndrome - Zenkel, Matthias; Krysta, Anita; Pasutto, Francesca; Jünemann, Anselm; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2011)
Purpose. Pseudoexfoliation (PEX) syndrome/glaucoma is a complex, late-onset disorder of the elastic fiber system. Strong genetic risk is conferred by the lysyl oxidase-like 1 (LOXL1) gene, but additional comodulating factors are necessary for the manifestation of the disease. The aim of this study was to analyze the effect of various PEX-associated pathogenic factors on the genotype-correlated expression of LOXL1 and elastin-related genes. Methods. Cultured human Tenon's capsule fibroblasts with high- and low-risk LOXL1 haplotypes were exposed to transforming growth factor (TGF)-?1, interleukin (IL)-6, homocysteine, oxidative stress, hypoxia, or ultraviolet (UV) radiation. Changes in the expression of LOXL1 and elastic constituents of PEX material and TGF-?1 were assessed by quantitative real-time PCR, Western blotting, immunohistochemistry, and electron microscopy. Results. Treatment of fibroblasts with TGF-?1, oxidative stress, UV light, and hypoxia induced a significant increase in expression levels of LOXL1 and elastic proteins, whereas the effect of IL-6 was limited to induction of elastic constituents. Immunohistochemistry and electron microscopy confirmed an upregulation of LOXL1 and elastic fiber proteins and their assembly into extracellular microfibrillar networks with focal aggregation of microfibrils into PEX-like fibrils on stimulation with TGF-?1 and oxidative stress. Basal and stimulated expression of LOXL1 mRNA and protein was slightly decreased in cells carrying the high-risk compared with the low-risk haplotype of LOXL1, but the differences between groups were statistically not significant. Conclusions. The findings support the notion that both genetic and nongenetic fibrogenic factors, particularly TGF-?1 and oxidative stress, may cooperate in the stable accumulation of PEX aggregates.
EVALuna2:9087

Relationship between the area of isopters and Vigabatrin dosage during two years of observation - Nowomiejska, Katarzyna; Jedrych, Marian; Brzozowska, Agnieszka; Rejdak, Konrad; Zarnowski, Tomasz; Koss, Michael J.; Ksiazek, Katarzyna; Ksiazek, Piotr; Maciejewski, Ryszard; Jünemann, Anselm; Schiefer, Ulrich; Rejdak, Robert (Bmc Ophthalmology, 2014)
The aim of the study was to evaluate the relationship between the area of isopters obtained using semi-automated kinetic perimetry (SKP) and Vigabatrin dosage in epilepsy patients with pretreatment baseline examination during 2-years of the follow-up.29 epilepsy patients were included into the study, but 15 individuals were excluded due to cognitive impairment, intracranial pathologies or eye diseases. Finally, 14 patients were examined with SKP before VGB treatment and after 6, 12, 18, and 24 months. Reaction time (RT)-corrected areas of three isopters (III4e, I4e and I2e) were measured for each of five examinations and compared intra-individually during 2-years period. Additionally, six epilepsy patients on other antiepileptic drugs were examined five times with SKP as a control.There was a significant decrease of I2e, I4e and III4e isopters' area during the follow-up of two years. Correlation was found between the I2e isopter's area and both cumulative dose and mean daily dose of VGB. With increasing RT, there was decreasing of all isopters' area in patients receiving VGB. In epilepsy patients who were not receiving VGB, there were no significance differences in isopters' area during follow-up.There was attenuation of area of III4e, I4e and I2e isopters obtained with SKP during a period of 2 years. RT, the cumulative dose and the mean daily dose of VGB influenced isopters' area obtained with SKP.
EVALuna2:21146

Reproducibility of Multifocal Erg Responses in Patients and Healthy Subjects - Link, B.; Ruehl, S.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: clinical

Retinal disorders in northern Brazilian patients treated with chloroquine assessed by multifocal ERG - Raster, M.; Horn, Folkert; Jünemann, Anselm; Rosa, A. A. M.; Souza, G. S.; Gomes, B. D.; Lima, M. G.; Silveira, L. C. L.; Kremers, Jan (Documenta Ophthalmologica, 2011)
The effects of chloroquine intake on the retinal function in a Brazilian population of patients were assessed by multifocal electroretinography. Twenty-four randomly chosen eyes of patients treated with chloroquine for rheumatoid arthritis and systemic lupus erythematosus were examined using multifocal electroretinography (mfERG). Control measurements were acquired from 21 randomly chosen eyes of age-matched healthy subjects. None of the study participants had an inherited retinal disease or a Snellen visual acuity reduced to less than 20/40. In patients and control subjects, cumulative chloroquine dose, total daily dose, duration of treatment, retinal examination, visual field defects, visual acuity, and the mfERG were assessed. The average amplitudes and implicit times of the N1, P1, and P2 components of the mfERGs were measured in the central hexagon (R1) and in five rings (R2-R6). The values measured in patients and normal subjects were compared. The P1 amplitudes in R2 were significantly decreased in the patients. In addition, the amplitudes of N1 and N2 in R1 were significantly smaller in the patients. The implicit times of none of the components were significantly different between patients and controls. The response amplitude was not significantly correlated with cumulative dose and duration of intake. There was no correlation with retinal appearance, visual field, and visual acuity. In agreement with earlier data, the central mfERG amplitudes were decreased in chloroquine patients indicating functional alterations in the retina. These changes are also present in a Brazilian population suggesting that the effects of chloroquine are general and that genetic background and life circumstances probably have, if at all, only little effect.
EVALuna2:21006

Solitary sarcoid granuloma of the iris mimicking tuberculosis: a case report - Rejdak, Robert; Pogorelov, Pavel; Mardin, Christian; Szkaradek, Malgorzata; Jünemann, Anselm (Journal of Ophthalmology, 2014)
Introduction. We report a case of a male patient presented with sarcoid lesions of the iris and conjunctiva, mimicking tuberculosis due to epithelioid cell granulomas with small central necrosis in conjunctival biopsy. Patient. A 25-year-old man was referred to our department for further management of an "iris tumor with iridocyclitis" in his right eye. Initial examination showed an isolated vascular tumor of the iris and ciliary body with anterior uveitis and mutton-fat keratic precipitates, suggesting the diagnosis of a granulomatous disease. Conjunctival biopsy revealed granulomatous epithelioid cell inflammation with small central necrosis without acid-fast bacilli. Extensive systemic examination, including bronchoscopy and transbronchial biopsy, provided the diagnosis of sarcoidosis stage 2 with pulmonary involvement, thus ruling out tuberculosis. Systemic and local steroid therapy was initiated, leading to complete recovery of our patient with complete disappearance of the iris lesion and improvement of the pulmonary function. Conclusion. Although noncaseating epithelioid cell granulomas are typical for sarcoidosis, small central necrosis can be found in some granulomas, leading to presumption of tuberculosis. Extensive systemic checkup in cooperation with other specialists is essential to confirm the correct diagnosis and to initiate the appropriate therapy.
EVALuna2:21186

The Effect of Long-term Antiglaucomatous Drug Administration on Central Corneal Thickness - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Mardin, Christian; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Braun, Joachim M.; Lämmer, Robert (Journal of Glaucoma, 2016)
To evaluate rates of changes per year of central corneal thickness after antiglaucomatous drug administration with ?-blockers, prostaglandin analogs, and carbonic anhydrase inhibitors monotherapy and combined topical antiglaucomatous therapy, in a cohort of patients with ocular hypertension, glaucoma suspects, and patients with perimetric glaucoma as compared with normal controls.This retrospective single-center study included 130 eyes as healthy controls, 121 eyes of ocular hypertensive patients, 105 eyes of glaucoma suspects, and 49 eyes of perimetric glaucoma patients. All patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and optical coherence pachymetry (OCP; Heidelberg Engineering). The cohort was divided into 8 groups on the basis of topical antiglaucomatous medication. Linear regression analysis was conducted to analyze the relationship between central corneal thickness and exposure to antiglaucomatous medication during the follow-up.Central corneal thickness did not change during the follow-up for investigated diagnostic subgroups. There was a statistically significant decrease in central corneal thickness for eyes treated with prostaglandin monotherapy (-3.1 ?m/y for left eye), and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers (-5.8 and -3.8 ?m/y for right and left eye, respectively).We recommend regular measurements before and during therapy with prostaglandin monotherapy and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers. Follow-up intraocular pressure measurements may be underestimated for eyes treated with the aforementioned treatment regimens if central corneal thickness is not measured on a regular basis.
EVALuna2:21177

The Erlangen Glaucoma Registry: a Scientific Database for Longitudinal Analysis of Glaucoma - Lauterwald, Frank; Neumann, Christoph; Lenz, Richard; Jünemann, Anselm; Mardin, Christian; Meyer-Wegener, Klaus; Horn, Folkert (2011)
UnivIS-Import:2017-12-18:Pub.2011.tech.IMMD.IMMD6.theerl
Keywords: Glaukom; Elektronische Patientenakte; Register; Längsschnittuntersuchung; Wissenschaftliche Datenbank; Relationale Datenbank

The photopic negative response of the blue-on-yellow flash-electroretinogram in glaucomas and normal subjects - Wakili, Nina; Horn, Folkert; Jünemann, Anselm; Nguyen, Nhung; Mardin, Christian; Korth, Matthias-Johannes; Kremers, Jan (Documenta Ophthalmologica, 2008)
The photopic negative response of the flash-electroretinogram driven by the middle- and long-wavelength cones has been shown to be reduced in non-human primates with experimental glaucoma and in human patients with glaucoma. The photopic negative response for the blue-sensitive response has been studied using a blue-green silent-substitution-technique on a red background. The aim of this study was to re-evaluate the value of the photopic negative response of the blue-sensitive pathway in glaucoma using a conventional flash-electroretinogram. In 37 eyes of 37 controls (age: 53 +/- 13.6 years) and 37 eyes of 37 patients with open-angle glaucoma of different perimetric visual field defects (age: 58.3 +/- 10 years; MD: 11.7 +/- 6.7 dB) of the Erlangen glaucoma registry Ganzfeld flash-electroretinograms (LKC, UTAS 3000) were recorded using blue Xenon-flashes of increasing photopic luminance (0.013, 0.018, 0.030, and 0.052 cd s/m(2); 440 nm) on a bright yellow background (238 cd/m(2); 550 nm) after 2 min of light adaptation. Amplitudes and implicit times of the photopic negative response and of L&M-cone- and S-cone-driven b-waves were compared between glaucomas and controls for all flash energies (unpaired t-test). The amplitudes of the photopic negative response were significantly reduced in glaucoma patients for all flash energies (P < 0.001). The implicit times of L&M-cone-driven b-wave (0.013, 0.018, 0.030, and 0.052 cd s/m(2)) and S-cone-driven b-wave (0.030 and 0.052 cd s/m(2)) were significantly prolonged in glaucoma patients (P < 0.05). The changes in these implicit times, however, are very small (1.5 ms or less). The other measures did not differ significantly. The amplitude of the photopic negative response and the implicit times of the L&M-cone and S-cone b-wave in the same responses of the blue-on-yellow flash-electroretinogram are potentially useful in the evaluation of inner-retinal function in glaucoma.
Keywords: electroretinogram; glaucoma; L&M-cone; photopic negative response; S-cone

Time course of induced astigmatism after canaloplasty - Moelle, Michaela C.; Cursiefen, Claus; Rejdak, Robert; Horn, Folkert; Jünemann, Anselm (Journal of Glaucoma, 2014)
To study the changes in astigmatism after canaloplasty and to analyze its correlation with long-term intraocular pressure (IOP) results.Twenty-six eyes of 26 consecutive patients with primary open-angle glaucoma (n=14) and pseudoexfoliative glaucoma (n=12) undergoing canaloplasty were included in this retrospective study. Canaloplasty comprised of 360-degree catheterisation of Schlemm canal by means of a flexible microcatheter with distension of the canal by 2 tensioning 10-0 polypropylene sutures. Primary outcome measures included IOP, glaucoma medication usage, astigmatism, and adverse events at 2, 4, 12, and 24 weeks postoperatively.The mean preoperative IOP was 21.1±5.8 mm Hg. The mean IOP decreased to 14.25 ±4.3 mm Hg at 6 months. Mean astigmatism preoperatively was 0.77±0.5 D, which increased to 3.3±1.7 D at 2 weeks postoperatively (P<=0.05; Wilcoxon-test). Thereafter, the astigmatism underwent a spontaneous decline, reaching 1.9±0.8 D at 4 weeks and 1.2±0.74 D at 12 weeks postoperatively. Best-corrected visual acuity did not change significantly. Six months after canaloplasty, mean astigmatism reached the preoperative range of 0.86±0.52 D. Astigmatism at 2 weeks correlated significantly and inversely with IOP at 6 months (r=0.59, P=0.005; Spearman).The change of astigmatism after canaloplasty follows a clear time course with a maximum at 2 weeks reaching preoperative values at 6 months. The amount of surgically induced astigmatism might be helpful to predict outcome of canaloplasty in terms of IOP reduction.
EVALuna2:21164

Unilateral retinitis pigmentosa: 30 years follow-up - Weller, Julia M.; Michelson, Georg; Jünemann, Anselm (BMJ Case Reports, 2014)
This case report depicts the clinical course of a female patient with unilateral retinitis pigmentosa (RP), who presented first in 1984 at the age of 43 years. At the beginning, there were cells in the vitreous leading to the diagnosis of uveitis with vasculitis. Within 30 years, the complete clinical manifestation of RP developed with bone spicule-shaped pigment deposits, pale optic disc, narrowed arterioles, cystoid macular oedema, posterior subcapsular cataract, concentric narrowing of the visual field and undetectable electroretinogram signal. At the age of 72 years, there are still no signs of retinal dystrophy in the other eye.
EVALuna2:21211